Ecology, distribution, recruitment, and fishery of Conch (Gastropoda Stromnidae) in the intertidal zone of Nueva Valencia, Guimaras, Philippines - Diamante, Rose Ann M
Macroinvertebrates from Family Strombidae locally known as "sikad-sikad" are one of the major gleaned species in the coastal municipality of Nueva Valencia in Guimaras Island, Philippines. However, studies on its biology, ecology and fishery are scarce and have not been documented in this specific area. Hence, this study investigated the ecology, abundance,distribution, recruitment, and fishery of conch species from Family Strombidae in the three coastal barangays (Pandaraonan, Dolores, and Tando) of Nueva Valencia. The ecological aspects were assessed for three habitat types (seagrass beds, bare sand, and edges of mangrove areas) within each of the barangay locations using the quadrat method. The gleaning fishery was assessed via survey sing a structured questionnaire and catch data from contracted gleamers. a total of 319 conch individuals were sampled belonging to seven species (Canarium erythrinum, Canarium labiatum, Canarium mutabile, Canarium urceus, Conomures luhuanus, Gibberelus gibbosus, and Laevistrombus canarium). The distribution of these species varied across habitats but were found most abundant in Enhalus acoroides and Thalassia hemprichii seagrass beds and showed patchy distribution either exhibiting regular or clumping patterns within this habitat. Shell lengths ranged from15-50 mm with C. mutabile being the smallest C. luhuanus and L. canarium as the largest species. Temporal assessment at one site (i.e. seagrass beds of Dolores0 showed no significant variation in the abundance and sizes of adult conch species across monitoring months. However, conch juveniles assessed showed increasing trend in shell length (5, 8, and 12 mm) but with decreasing density (103, 104, and 90 individuals/m ²) throughout the assessment in February, April, and June, respectively. Conchs are very valuable fishery species with distinct distribution especially in a seagrass areas, show no apparent seasonality, but threatened by high exploitation rates. Results of this study will be useful for establishing relevant regulations and fisherues management to ensure sustainability of this important fisheries resource.